Routes - Campbell, Peter; Vuković, Krešimir (Liverpool University Press, 2022)
The waters of the Mediterranean may be the greatest museum of Antiquity. Scattered across the seafloor are shipwrecks from every time period. Cargos of wine, oil, and fish were transported in clay amphoras, which are found stacked in the sands or spilling down submarine cliffs in waterfalls of ceramics. There are also other items: lamps, cooking pots, anchors, and fragments of everyday life. These objects tell human stories, which archaeologists carefully tease out of the material record. It is sometimes possible to identify the ship’s previous ports of call, their home port, or their intended destination. Since the first shipwreck discoveries by early divers, a database of Mediterranean shipwrecks has slowly been built and recreated the paths that the ships navigated. 1 It reveals a ‘globalized’ ancient Mediterranean which spread cargo, languages, religions, war, and ideas. The efflorescence of ship-borne connectivity was possible through the creation and sharing of routes.